Dementia : prevalence and risk factors - Akter, Seikh Farid Uddin; Abdul Rani, Mohammed Fauzi; Nordin, Mohamad Sahari; Ab Rahman, Jamalludin; Md Aris, Mohd Aznan; Rathor, Mohammad Yousuf (International Review of Social Sciences and Humanities, 2012)
The increasing prevalence of dementia already has dramatic effects on lives of millions of people across the regions and on public health costs. There is no cure yet but much can be done to improve the quality of life of people with dementia and the families who care for them. An extensive review of the literature in several pertinent areas of inquiry that may determine and delineate the prevalence, potential risk factors related to dementia was undertaken. The overall prevalence for males and females doubled for every five years increase in age after the age of 65. It is largely a disease of older people, but 2% of those affected were under 65 years of age. Results highlight a number of risk factors associated with dementia. Inter alia, these include physical activities, education, occupation, stress, cholesterol and APOE gene. Dementia is increased in certain population and the trend is on the rise. A number of risk factors associated with dementia are modifiable and may have potential as strategies useful in preventing or delaying dementia among elderly subjects. Further research is needed to determine the validity and strength of associations of risk factors of dementia including ascertainment of its causality.